Nanotechnology-Based Formulations of Curcuma xanthorrhiza for Modern Herbal Therapy: A Narrative Literature Review: Formulasi Berbasis Nanoteknologi Curcuma xanthorrhiza Roxb. sebagai Terapi Herbal Modern: Tinjauan Literatur Naratif - Hanif Luthfiansyah Azhar; Hannie Fitriani; Yandi Syukri; Arba Pramundita Ramadani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2026)
Background: Curcuma xanthorrhiza Roxb. (temulawak) is an Indonesian medicinal plant with documented antibacterial, anti-inflammatory, antioxidant, hepatoprotective, and anticancer activities, yet its major active compounds, curcuminoids and xanthorrhizol, suffer from poor aqueous solubility, low stability, and very limited oral bioavailability. Objectives: This study aims to review nanotechnology-based formulation strategies developed to overcome the biopharmaceutical limitations of C. xanthorrhiza and to optimise its potential as a modern herbal therapy. Methods: A narrative literature review was conducted using national and international articles published mainly between 2015 and 2025 that were retrieved from PubMed, ScienceDirect, and Google Scholar with keywords related to Curcuma xanthorrhiza, nanoformulation, and drug delivery systems; data were qualitatively summarised according to type of nanoformulation, physicochemical characteristics, and in vitro or in vivo biological activities. Results: Various nanotechnology-based delivery systems were identified, including nanosuspensions, nanoemulsions, Solid Lipid Nanoparticles (SLN), Self-Nanoemulsifying Drug Delivery Systems (SNEDDS), Solid-SNEDDS, nanogels, polymeric nanoparticles, and green-synthesised metallic nanoparticles; these formulations consistently reduced particle size to the nanometre range, improved solubility and chemical stability, increased entrapment efficiency, and enhanced pharmacological effects such as anti-inflammatory, antioxidant, antimicrobial, and anticancer activities compared with conventional extracts. Conclusions: Nanotechnology-based formulations of Curcuma xanthorrhiza represent a promising strategy to improve the efficacy, safety, and practicality of temulawak as a modern herbal medicine, and further well-designed preclinical and clinical studies are required to confirm their therapeutic advantages.